THE STRATEGIES OF AL-ISTIQOMAH NGATA BARU MODERN ISLAMIC BOARDING SCHOOLIN APPLYING ENGLISH SPEAKING SKILL TO SANTRI - fajar, fajar; yuni amelia (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2020)
In improving the English language skills of students, the Pondok Pesantren modern Al-istiqamah Ngata Baru has a language strategy. Students are required to communicate using English. However, in fact there are still some students whose English is still weak and left behind. The purpose of this study was to determine the strategy of the modern Al-istiqamah Ngata Baru Islamic boarding school in applying the speaking skills of the students. This research is used qualitative research. The research subjects were the head of the language field, the English teacher, the dormitory musyrif, the CLI (Central Language Improvement) board, and the students of the Al-istiqamah Ngata Baru Modern Islamic Boarding School. The technique used in determining the research subject is purposive sampling technique. Data collection techniques by interview, observation, and documentation. The data analysis techniques used were data collection, data reduction, data presentation, and verification. The results of this study indicate that the application of the strategy in English at Pondok Pesantren Modern Al-istiqamah Ngata Baru has been going well. With the English language strategy, the students 'English language skills continue to improve and with it the students understand better the lessons in class and the students' achievement increases, and they are able to win the English competition.